Non-destructive Evaluation of the Quality Characteristics of Pomegranate Kernel Oil by Fourier Transform Near-Infrared and Mid-Infrared Spectroscopy - Okere, Emmanuel E.; Arendse, Ebrahiema; Nieuwoudt, Helene; Perold, Willem J.; Opara, Umezuruike Linus (Frontiers in Plant Science, 2022)
The pomegranate kernel oil has gained global awareness due to the health benefits associated with its consumption; these benefits have been attributed to its unique fatty acid composition. For quality control of edible fats and oils, various analytical and calorimetric methods are often used, however, these methods are expensive, labor-intensive, and often require specialized sample preparation making them impractical on a commercial scale. Therefore, objective, rapid, accurate, and cost-effective methods are required. In this study, Fourier transformed near-infrared (FT-NIR) and mid-infrared (FT-MIR) spectroscopy as a fast non-destructive technique was investigated and compared to qualitatively and quantitatively predict the quality attributes of pomegranate kernel oil (cv. Wonderful, Acco, Herskawitz). For qualitative analysis, principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) was applied. Based on OPLS-DA, FT-MIR spectroscopy resulted in 100% discrimination between oil samples extracted from different cultivars. For quantitative analysis, partial least squares regression was used for model development over the NIR region of 7498–940 and 6102–5774 cm-1 and provided the best prediction statistics for total carotenoid content (R2, coefficient of determination, RMSEP; root mean square error of prediction, RPD; residual prediction deviation) (R2 = 84.38, RMSEP = 0.019, RPD = 2.28). In the MIR region of 3996–1118 cm-1, models developed using FT-MIR spectroscopy gave the best prediction statistics for peroxide value (R2 = 91.99, RMSEP = 1.05, RPD = 3.54) and refractive index (R2 = 91.27, RMSEP = 0.0002, RPD = 3.43). These results demonstrate the potential of infrared spectroscopy combined with chemometric analysis for rapid screening of pomegranate oil quality attributes.